Exporting Jobs?: The Impact of Import Competition on Employment and Wages in U. S. Manufacturing - Revenga, A. L. (Quarterly Journal of Economics, 1992)
This paper investigates the effect of increased import competition on U. S. manufacturing employment and wages, using data for a panel of manufacturing industries over the 1977–1987 period. The empirical analysis uses previously unavailable industry import price data and an instrumental variables estimation strategy. The estimates suggest that changes in import prices have a significant effect on both employment and wages. The dramatic appreciation of the dollar between 1980 and 1985 is estimated to have reduced wages by 2 percent, and employment by 4.5–7.5 percent on average in this sample of trade-impacted industries.